Examining the impacts of COVID-19 on dividend payouts: evidence from Singapore stock market - Fan, Shuting (Nanyang Technological University, 2024)
With the onset of COVID-19, an unprecedented global health crisis that has affected numerous countries on their domestic productivities, greater volatility was observed in various stock markets. Any dividend decision change can serve as a signal to convey essential information to investors. This study aims to examine the impacts of COVID-19 on dividend payments in the context of Singapore. Using panel data analysis, we found that Singaporean companies had the lowest dividend payout in 2020 in general. By categorising Singaporean companies into three overarching industries – manufacturing, utility, and service, we found an immediate negative impact of COVID-19 on dividend payouts in the utility sector. However, firm characteristics such as firm profitability and size play a more significant role in influencing dividend payouts were observed within the manufacturing and service sectors during the pandemic.